1
$\begingroup$

Let $\{S_n\}$ be a symmetric random walk such that $S_0 = a$ for some $0 < a < K$. Let $T$ be the stopping time when the walk reaches $0$ or $K$. Show $$M_n = \sum_{i = 0}^n S_i - \frac{1}{3}S^3_n $$ is a martingale and deduce that $\mathbb{E}\bigg[ \sum_{i = 0}^T S_i \bigg] = \frac{1}{3}(K^2-a^2)a + a$.

So far I have tried showing it is both a submartingale and supermartingale and also have tried $\mathbb{E}[M_{n+1} - M_n \mid X_0,...,X_n] = 0 $ approach. I think the error is in my computing so $S^3_n$ but I am not getting that it is a martingale. The second part just seems to be that I need to apply the martingale convergence theorem/optional stopping time.

I got that $$S_n^3 = \sum_{i=0}^n X_i^3 + 6\bigg(\sum_{i < j}X_i^2X_j + \sum_{i < j} X_iX_j^2 + \sum_{i < j < k}X_iX_jX_k \bigg)$$.

Also I know that $\{S_n\}$ by itself is a martingale since $p = \frac{1}{2}$. So now $$\begin{align*} M_{n+1} - M_n &= X_{n+1} + \frac{1}{3}(S_{n+1}^3 - S_n^3) \\ &= X_{n+1} + \frac{1}{3}\bigg(X_{n+1}\sum_{i = 0}^nX_i + X_{n+1}^2\sum_{i = 0}^nX_i + X_{n+1}\bigg[\sum_{i = 0}^n X_i \bigg( \sum_{j=i+1}^n X_j\bigg)\bigg]\bigg) \end{align*}$$ .

Which seems quite incorrect.

$\endgroup$
2
$\begingroup$

Clearly,

$$S_{n+1}^3 = (S_n+X_{n+1})^3 = S_{n}^3 +3 S_n X_{n+1}^2 + 3S_n^2 X_{n+1}+X_{n+1}^3$$

which implies ("take out what is known"/"pull out")

$$\mathbb{E}(S_{n+1}^3 \mid \mathcal{F}_n) = S_n^3+3 S_n \underbrace{\mathbb{E}(X_{n+1}^2 \mid \mathcal{F}_n)}_{=\mathbb{E}(X_{n+1}^2)=1} + 3 S_n^2 \underbrace{\mathbb{E}(X_{n+1} \mid \mathcal{F}_n)}_{=\mathbb{E}(X_{n+1})=0} + \underbrace{\mathbb{E}(X_{n+1}^3 \mid \mathcal{F}_n)}_{=\mathbb{E}(X_{n+1}^3)=0}$$

i.e.

$$\mathbb{E}(S_{n+1}^3 \mid \mathcal{F}_n) = S_n^3 + 3 S_n.$$ Using this equation, you shouldn't have much trouble to verify the martingale property of $(M_n)_{n \in \mathbb{N}}$.

$\endgroup$
  • $\begingroup$ I definitely did some calculating wrong. For the second part am I correct that this is an application of optional stopping theorem? It's not quite set up for $\mathbb{E}[M_0] = \mathbb{E}[M_T]$ But it is $\mathbb{E}[M_T + \frac{1}{3}S^3_T] $. but here $\mathbb{E}[M_0] = a - a^3/3$. $\endgroup$ – all.over Dec 6 '18 at 21:53
  • $\begingroup$ Sorry made edits to the comment above, hit add before I was done. $\endgroup$ – all.over Dec 6 '18 at 21:58
  • $\begingroup$ @all.over Well you will need to compute $E (S_T^3) $... to this end use $E (S_T)=0$ to find $P (S_T=0) $ and $P (S_T=K) $ $\endgroup$ – saz Dec 6 '18 at 22:34
  • $\begingroup$ It won't let my at people for some reason. Anyway, isn't $E(S_T) = E(S_0) = a$ by the martingale property? $\endgroup$ – all.over Dec 6 '18 at 22:48
  • 1
    $\begingroup$ @all.over Yeah, sorry, that was a typo. $\endgroup$ – saz Dec 6 '18 at 23:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.